The Status of Women in Leadership - Alqahtani, Tahani (Archives of Business Research, 2020)
The Status of Women in Leadership Tahani H. Alqahtani PhD student, Management at Aberdeen University – Lecturer, College of Economics and Administrative Sciences at Imam Mohamed Ibn Saud University. Abstract Even though females have indeed entered jobs previously closed to them, many occupations remain as gender-gapped now as they were half a century ago. Gender-segregated employment patterns are so tenacious because, they are built into the very organizational fabric of work and the workplace. Descriptive stereotyping describes what men and women are like and prescriptive stereotyping defines defining what women and men should be like. This literature review provides a broad understanding of the gender differences in leadership and the gender gap in organization. This literature review founds that gender-segregated employment patterns are so tenacious because they are built into the very organizational fabric of work and the workplace. Introduction The current literature concerning leadership from a variety of Eastern and Western countries highlights that, regardless of a recent global increase in the number of females entering the labour market, only a small number of professional women hold top management or leadership positions. In spite of the fact that the growth pattern of women in the labour force and their representation in leadership roles does differ across countries and regions, and although a number of women in leadership positions worldwide are making contributions both within and beyond their communities (Percupchick, 2011), the overarching observation can be made that a substantive gender gap exists in female’s representation in relation to leadership positions and decision-making across many sectors of society (Catalyst, 2016). Moreover, studies indicate that a large number of sometimes highly qualified women are choosing to step down from positions of authority and leave their careers (Rabas, 2013). This literature review provides a broad understanding of the gender differences in leadership and the gender gap in organization. Literature Review Research has identiﬁed the reasons for the persistence of women having a less expressive presence in management and leadership positions (Acker, 1991; Kolb et al., 1998; Simpson, 2004; Williams, 2001; England, 2010; Kellerman and Rhodes, 2014; Gipson, et al., 2017). Among these, the existence of a male-normed corporate culture and organizational structure is posited as a formidable obstacle to female progress in the workplace. The literature abounds with evidence of the way organizational norms, values and structures, disadvantage females in their career advancement at the institutional level (Morrison, 2012; Keohane, 2014). Looking specifically at the field of academia, for Nguyen (2012), “Policies and process in higher education can act as barriers against women assuming leadership and management positions” (p. 127). Acker (1990) suggests the existence of an organizational attitude behind these gender contrasts as a result of organizational structure, rather than any differences held to exist in the characters of males and females. Goveas and Aslam (2011, p. 236) state that a further important factor with the potential to hinder female's opportunities for development consists of “the unavailability of structured human resource policies and strategies addressing women workers, [which] has proven to be a major obstacle to women’s progress and development”. Referring specifically to the field of educational management, for Sui Chu Ho (2015), “Gender inequalities in staff recruitment, appointment and promotion exist in educational institutions, such as universities” (p. 87). She goes on to note how this evidence and claim to support it are actually routinely dismissed, both by those in authority and the general public. It is likely that hierarchal organizational structures create a setting in which women feel out of place due to gender variances (Morrison, 2012; Al-Shanfari, 2011; Keohane, 2014), resulting in many females stepping down or leaving from a post in a workplace at which their leadership abilities are being questioned. This conflict is further compounded by many jobs being designed around men’s objectives, and that many organizations are reluctant to support women within their workforce when potential career conflicts arise (Kellerman, and Rhode, 2012). Therefore, the ideal worker is male: “Images of men’s bodies and masculinity pervade organizational processes, marginalizing women and contributing to the maintenance of gendered segregation in organisations” (Acker 1990, p. 139). A key impact of organizational masculinity is the emotional labor expended by women in order to succeed. Connell (1987) states that gendered structures and practices operating within organizations result in very different career experiences and outcomes for women and men, and the most senior organizational positions are considered sites of hegemonic masculinity. Thus, organizational structure is not gender neutral and organizational culture reflects the wishes and needs of powerful men. In reviews of research into gender and leadership, limiting women’s progress in organizations is a well-documented phenomenon, including the persistence of gender stereotypes. Kanter (1977) identifies the ‘masculine ethic’ as part of the early image of leaders and managers. This masculine ethic elevates the traits assumed to be exclusive to men as requirements for effective management: a tough-minded approach to problems; analytical planning abilities; a capacity to set aside personal emotional considerations in the interests of task accomplishment; and cognitive superiority in problem-solving and decision-making (Kanter, 1977). Thus, even with regards to Kanter, (1977), although social construction presumes that these traits and characteristics supposedly belong to males only (or are at least more likely to be held by males), if practically all leaders and managers are men from the beginning, it should come as no surprise that when females attempt to enter leadership or management occupations the masculine ethic is invoked as an exclusionary principle Acker (1991) sees the ‘masculine ethic’ referred to earlier as the structural basis of organizations, in the sense that allegedly ‘masculine characteristics’ are built into the very fabric of organizations. As a result, the workplace itself is stacked against the equalization of opportunities for women. Acker (1991, p. 289) defines gendered organizations as occurring when “advantage and drawback, control and exploitation, emotion and action, identity and meaning, are patterned through and in terms of a distinction between female and male, feminine and masculine”. Thus, masculinity assumes control of the workplace environment or the business sphere in the subtlest of ways (Acker, 1991). Additionally, masculinity also appears to affect employees’ characters. The preferred employee presents her/himself as a masculine character in choice of clothes, language, and presentation (Acker, 1991). Furthermore, job opportunities and hierarchies are also filled in accordance with gender preferences, meaning that the positions should concur with what is deemed relevant and suitable for the gender that fills them (Kolb et al., 1998). In this way, gender implications have negatively influenced the progress of women in their working lives (Acker, 1991). Informal occupational segregation due to gender stereotypes as well as the gender biases commonly held by the wider society entail the trend of hiring women and men in different types of working areas and positions (Fitzsimmons, Callan, and Paulsen, 2014). Simpson (2004) argues that gender representation in social discourse and social perceptions of gender play a significant role in sustaining and promoting gendered employment. Consequently, these biased stereotypes, embedded in deep-rooted ideologies, automatically view job placement through the lens of gender (Simpson, 2004). Thus, work related to masculine organizations draws on the notion of a job requiring allegedly masculine qualities such as analytical skills, assertiveness and physical strength, in turn reinforcing more the idea of being ‘manliness’ being something distinct and unattainable for women. Unsurprisingly, as Britton and Logan (2008) note, these jobs, in turn, naturally attract more male applicants than females. At the same time, stereotypical assumptions that females pay more attention to detail, are more caring, and place value on physical attractiveness confine them to roles as teachers, nurses, administrators, and jobs in the beauty industry (Britton and Logan, 2008). Moreover, men are more likely to be selected for any ‘male-type’ position in a company even when women and men possess the same qualifications because of the implicit bias that, like for like, men perform better than women (Omar and Davidson, 2001). This leads individuals to believe that women do not have the necessary skills and so are unable to work effectively in male-type jobs. For example, because women are associated with activities that do not involve much in the way of physical strength (such as taking care of their children and families), they have traditionally been considered a second choice to men when it comes to jobs that involve working outdoors (Britton and Logan, 2008). England’s (2010) research has shown that in the twentieth century women have progressed at a sluggish pace in terms of workplace equality. Despite the fact that females have indeed entered jobs previously closed to them, many occupations remain as gender-gapped now as they were half a century ago. Moreover, she notes that at any level of the employment pyramid, females continue to lag behind males in terms of authority and pay, regardless of the closing gap between men and women in workplace seniority and educational attainment. Acker (1990) argues that such gender segregated employment patterns are so tenacious because, as noted, they are built into the very organizational fabric of work and the workplace. Stereotyping means generalizing behavioural characteristics of groups of individuals and then applying the generalization to people who are members of the group (Heilman, 2012). Recently, researchers have investigated gender stereotyping by dividing the generalizations into two properties, descriptive and prescriptive. Heilman (2012) concentrated on the importance of each of those properties. Descriptive stereotyping describes what men and women are like and prescriptive stereotyping defines defining what women and men should be like. For instance, descriptive stereotyping of women creates negative expectations about a woman’s performance as a leader owing to there is a lack of fit between the characteristics assigned to traditionally male leadership roles and the societal roles assigned to females. Prescriptive stereotypes, or ascribing behaviors women ought to emulate, and the agentic characteristics of leadership create an incongruity with expected women behavior (Wynen et al., 2014). Furthermore, Heilman argues that irrespective of whether gender stereotyping is prescriptive or descriptive, the practice impedes the progress of females into leadership roles. One source for gender inequalities in the work force is gender stereotyping in the form of occupational segregation (Wynen et al., 2014). Occupational segregation occurs because there is a separation of women or men in certain occupations or employment sectors (Wynen et al., 2014). This gender separation is seen in occupations such as doctors , nursing, lawyers and teaching. Often, teachers or nurses are portrayed as women, while, lawyers and doctors are portrayed as men. According to scholars in social role theory, such as Franke, Crown, and Spake (1997) and Eagly (1987) gender stereotyping in certain occupations is deeply inherent in societal roles for female and male. Although both women and men have been shown to exhibit biases toward women in high management positions (Eagly and Carli, 2007; Ellemers, Rink, Derks, and Ryan, 2012; Ryan et al., 2011), Ellemers et al. (2012) pointed out that most individuals prefer to believe in a just world where gender differentiation is rare and success is based on merit; thus, in most instances, they will treat allegations of unequal treatment unfavourably. This result lead to fewer reports for fear of negative repercussions, and consequently inequity is often not noticed, challenged, or addressed (Ellemers et al., 2012). Moreover, Ibarra et al (2013) believe that when organizations advise females to seek leadership positions without addressing the subtle biases that exist in practices and policies, the companies undermine the psychological development that should take place to become a leader. Conclusion In conclusion, this literature review has outlined how women face obstacles in different organizational context, limiting their ability to achieve empowerment by aspiring to and achieving leadership. Historically, certain factors have hindered women from being accepted as leaders, regardless of their achievements, which leads to an underestimation of their capabilities. This under-representation of qualified women in leadership roles is symbolic of the gender gap in the workplace.